Pengaruh Tabel Top Covid Simulator Terhadap Pengetahuan Dan Sikap Anak Sekolah Dalam Pencegahan Covid 19 - Mohamad Roni Alfaqih; Bayu Akbar K; Angger Anugerah; Ainul Mufidah (Jurnal Kesehatan Manarang, 2023)
The most dangerous infectious disease that is currently being debated around the world is the Corona virus disease. The problems and challenges currently faced by educational institutions require prevention strategies by providing motivation as well as guidance and enthusiasm in the learning activities of elementary school students. The purpose of this study was to explore the effect of table top covid simulator on knowledge and attitude of elementary school students. Methods: Pre-experimental research using one group pre-test and post-test design. The population in the study was 120, and a sample of 38 elementary school students was obtained using a total sampling technique. The data collection technique uses a pre-post test which is carried out by assessing elementary school students regarding their attitudes and knowledge of preventing Covid-19 using a questionnaire guide. Data processing by editing, coding, scoring, and tabulating and analyzed by Paired T-Test. Results: This study shows that the statistical test results of the independent and dependent variables in this study are the significance value <0.05, which is 0.000 with a correlation coefficient value of 0.82, which means that there is an effect of the table top simulator on the knowledge and attitudes of elementary school students about preventing covid-19. Conclusion: Table top covid simulator can improve attitudes and knowledge about prevention of covid-19 in elementary school students, it has a positive impact on students in complying with health protocols and preventing infection transmission.